THE SCIENTIFIC BASE OF ECONOMIC DEVELOPMENT - Mahalanobis, P.C. (SCHOOL SCIENCE, 2012)
The essential characteristic of an underdeveloped country is an extremely low level of living, that is, inadequate supply of food, clothes, housing, drugs and other consumer goods, and also lackof facilities for education, care of health, social security, cultural amenities, etc., for the nation as a whole. It is possible to make available small quantities of consumer goods, by direct imports or by production, on a small domestic scale, with the help of imported machinery.